Hydrogen production by steam reforming of biomass-derived glycerol over Ni-based catalysts - Kim, Seung-hoon; Jung, Jae-sun; Yang, Eun-hyeok; Lee, Kwan-Young; Ju, Moon Dong (ELSEVIER, 2014)
The steam reforming of bio-glycerol for the production of hydrogen has been investigated in a fixed-bed reactor containing spherical particle of Ni supported on gamma-Al2O3 as catalyst. Several catalysts were prepared by the dry impregnation method at different calcination temperatures (750-950 degrees C) with/without the addition of various alkaline promoters (K, Ca, Sr). The physical and chemical properties of the prepared catalysts were characterized by nitrogen (N-2) physisorption, X-ray diffraction (XRD), temperature-programmed reduction, thermogravimetric analysis, scanning electron microscopy-energy dispersive X-ray spectroscopy and transmission electron microscopy techniques. The Ni/gamma-Al2O3 catalysts showed a high glycerol conversion and hydrogen selectivity, however they gradually deactivated due to the formation of carbon over those catalysts. Nevertheless, it was found that the catalysts calcined at high temperatures could inhibit the formation of carbon without affecting the glycerol conversion and hydrogen selectivity. The addition of alkaline promoters caused a slight decrease in the glycerol conversion, but also reduced the formation of carbon and thereby increased the long-term stability of the catalyst. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: THERMODYNAMIC ANALYSIS; THERMAL-STABILITY; SURFACE-AREA; SUPPORTS; ADDITIVES; ETHANOL; MG; ZR